An Inquiry on Japanese Language Education in Indonesia: A focus on the curriculum and its’ implementation - Kusumawati, Mutia (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2019)
The number of Japanese language learners in Indonesia has reached second place in the world (The Japan Foundation, 2015). However, Japanese language skills of learners in Indonesia are still very far behind from other countries, especially China and South Korea. Therefore, this study aims to discuss the causes of the lack of development on Japanese language learning abilities in Indonesia with the curriculum approach used. To answer these problems, author analysed data by The Japan Foundation, interviewed Japanese language teachers at one national high school in Bandung, and reviewed the curriculum that was being used. The results showed that most of Japanese language learners in Indonesia are at the secondary education level and mostly are high school students. However, the purpose of the Japanese language teaching curriculum in high schools in Indonesia does not require students to master Japanese to the upper level. Therefore, even though the number of Japanese language learners in Indonesia is large, but because the target of language acquisition is low, the Japanese language ability also tends to be low.